NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU INSECURITY IS MY MIDDLE NAME DAN RELEVANSINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Ibtisamah, Izzati; Nasoha, R. Ahmad Muhammad Mustain (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
This research aims to find out the character education values in the book Insecurity is My Middle Name by Alvi Syahrin and find out its relevance to Islamic religious education. The type of research used in this study is library research, where data sources are obtained from library research. The data collection technique uses documentation techniques, namely data collection obtained from primary data, namely the book Insecurity is My Middle Name by Alvi Syahrin, and secondary data, books that have similar discussions and can complement and answer problems. The data validity technique used is theoretical triangulation, while the analysis used is content analysis. The results showed that the character education values in the book Insecurity is My Middle Name by Alvi Syahrin are; Character (a) religious (b) Nationalist (c) Independent (d) cooperation (e) Integrity. The eleven character education values also have relevance to Islamic religious education, especially on the values of; (1) faith (2) Sharia (3) morals.